Child development and prematurity: a reflection on maternal knowledge and expectations - Maria Raquelle de Oliveira Melo; Izabella Santos Nogueira de Andrade (Universidade de Fortaleza, 2014)
Objective: To investigate maternal knowledge and expectations about the development of their premature children. Methods: Qualitative study, carried out at the Nucleus for Integrated Medical Attention (Núcleo de Atenção Médica Integrada - NAMI) of the University of Fortaleza (UNIFOR), Ceará, Brazil, in the period from February to December 2012, comprising mothers of premature children attended by the institution. Data collection took place by means of a semi-structured interview, which had as guiding questions: knowledge about the normal child development; relation between prematurity and development; possible implications to the development of premature infants; and the maternal expectations regarding their children's future. The following themes were considered: maternal knowledge about normal development; mothers' perceptions of the delays and compromises in the development process; and maternal expectations regarding the development evolution of their premature children. The interviews were transcribed and analyzed according to the content analysis technique. Results: Difficulties in knowledge related to the normal development and with regard to delays and compromises of premature child were observed. Maternal expectations concerning the evolution of their premature children's development process were considered satisfactory. The study emphasizes the role of the interdisciplinary team in the process of following up on the premature child's development, as well as the importance of this team for mothers. Conclusion: The interviewed mothers encountered difficulties in describing both the normal child development and the development associated to prematurity, and revealed positive expectations towards their children's future development. doi:http://dx.doi.org/10.5020/18061230.2013.p548